ANALISIS PERFORMA KINERJA TURBIN ANGIN SAVONIUS 2 SUDU - Basuki; Mohammad Munib Rosadi; Retno Eka Pramitasari; Fajar Satriya Hadi (Discovery, 2020)
Abstract: Renewable energy sources are energy sources that can replace the use and use of fossil energy sources where they are very abundant and have not been widely used for their existence. Therefore, to bring up new ideas in terms of creating or changing renewable energy, there needs to be a match between the education curriculum and market needs. So to arouse the enthusiasm and motivation of students in the teaching and learning process, especially in the energy conversion machine course for mechanical engineering students, it needs media and learning methods. The purpose of this research is to know how to design a savonius wind turbine props, and the working principle, and analyze the performance of the wind turbine. The sequence of the process of making savonius wind turbines comprises of making: (1) frameworks and machine tables, (2) chimneys, (3) duct, (4) installation of fans, (5) turbine holder (6) two blades savonius turbines and servo motor holder. The working principle of a wind turbine is a turbine rotation caused by the wind being transmitted to the generator rotor, where the generator has a copper coil that functions as a stator which will produce an electric voltage. From this research produced a savonius wind turbine tool which is used as a learning medium in the Mechanical Engineering Study Program. From the results of savonius type wind turbine test equipment produced the following data: maximum voltage of 10 volts, wind speed of 8.5 m / s, rotor generator rotation of 2734 rpm and power of 340 watts. Keywords: Energy, Turbine, Wind, Savonius Abstrak: Sumber energi terbarukan adalah sumber energi yang dapat menggantikan pemanfaatan dan penggunaan sumber energi fosil dimana keberadaannya sangat melimpah dan belum banyak digunakan akan keberadaannya. Oleh karena itu untuk memunculkan ide ide baru dalam hal menciptakan atau mengubah energi terbarukan ini perlu adanya kesesuaian antara kurikulum pendidikan dengan kebutuhan pasar. Maka untuk membangkitkan semangat dan motivasi mahasiswa dalam proses belajar mengajar khususnya dalam mata kuliah Mesin Konversi Energi bagi mahasiswa teknik mesin maka perlu media dan metode pembelajaran. Tujuan dari penelitian ini adalah mengetahui cara mendesain sebuah alat peraga turbin angin savonius, mengetahui prinsip kerja, dan menganalisa dari performa kinerja dari turbin angin tersebut. Urutan proses pembuatan turbin angin savonius adalah (1) pembuatan kerangka dan meja mesin, (2) pembuatan cerobong angin, (3) pembuatan duct, (4) pemasangan kipas angin, (5) pembuatan dudukan turbin, (6) pembuatan turbin savonius 2 sudu dan pembuatan dudukan motor servo. Prinsip kerja turbin angin adalah putaran turbin yang disebabkan oleh angin diteruskan ke rotor generator, dimana generator memiliki lilitan tembaga yang berfungsi sebagai stator yang akan menghasilkan tegangan listrik. Dari penelitian tersebut dihasilkan sebuah alat turbin angin savonius yang digunakan sebagai media pembelajaran di Program Studi Teknik Mesin. Dari hasil pengujian alat turbin angin tipe savonius menghasilkan data sebagai berikut: tegangan maksimal sebesar 10 volt, kecepatan angin 8.5 m/s, putaran rotor generator 2734 rpm dan daya sebesar 340 watt. Kata kunci: Energi, Turbin, Angin, Savonius